Hakikat Ilmu Psikolgi Positif: Tinjauan Filsafat Psikologi Pendidikan - Pambudhi, Yuliastri Ambar (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
This article discusses the nature of the philosophy of positive psychology in the context of education in Indonesia as an approach that aims to improve individual welfare and happiness holistically. The background of this study is the shift in the focus of psychology from curing mental illness to strengthening human potential, which is influenced by the humanistic approach and Aristotle's principle of eudaimonia. The main purpose of this paper is to describe the history of the birth of positive psychology, the philosophical dimensions that underlie it (ontology, epistemology, and axiology), and the direction of its development in Indonesia. The results of the study show that positive psychology has a major contribution to education, especially in building character, improving emotional well-being, and creating a supportive and meaningful learning environment. The concept of eudaimonia, Maslow's theory of needs, and the PERMA model are the main foundations in designing a learning approach that humanizes students. In Indonesia, the integration of local values, technology, and policies based on positive psychology is the strategic direction of its development. Thus, the philosophy of positive psychology provides a strong conceptual framework for adaptive, ethical, and sustainable education.